Eksplorasi Pengaruh Budaya Luar terhadap Kebiasaan Makan dan Gaya Hidup Remaja Suku Tengger: Studi Kualitatif: Exploring Cultural Influences on Eating Habits and Lifestyles Among Tengger Tribe Adolescents: A Qualitative Approach - Muniroh, Lailatul; Puspikawati, Septa Indra; Indriani, Diah; Abihail, Chrysoprase Thasya; Astuti, Ratna Dwi Puji; Ulaganathan, Vaidehi; Socadevia, Annisa (Amerta Nutrition, 2025)
Background: The eating habits and lifestyles of adolescents are strongly influenced by their culture. Adolescents from Tengger tribe may be affected by external cultural influences, as their area is a famous tourism destination. Objectives: The purpose of this study was to analyze the cultural influences on the eating habits and lifestyles of Tengger adolescents. Methods: This qualitative study involved interviews with 15 Tengger adolescents as key informants and the Head of Wonokitri Village. The variables examined include Tengger tribal culture, external cultural influences on eating habits, and various lifestyle aspects such as fashion choices, socialization behaviors, smoking, alcohol consumption, and gadget usage. Data were collected through in-depth interviews and observations of adolescent habits and analyzed using inductive analysis. Results: The results showed that Tengger adolescents still strongly adhere to their cultural customs. However, external cultural influences are also evident, as seen in their growing preference for fast food, evolving fashion styles, social interactions, smoking habits, alcohol consumption, and gadget use. Conclusions: The study concludes that, while Tengger adolescents continue to uphold their local culture, they are also indirectly influenced by external cultural elements in their eating habits, fashion choices, social behaviors, smoking, alcohol consumption, and gadget use. Therefore, it is recommended that Tengger adolescents critically evaluate which cultural influences have a positive impact on their lifestyles.